Escala de Atitudes em Relação à Inclusão: Versão Específica para cada Categoria de Deficiência - Omote, Sadao [UNESP]; Baleotti, Luciana Ramos [UNESP]; Chacon, Miguel Claudio Moriel [UNESP] (My University, 2014)
An adequate understanding of social attitudes toward inclusion is part of the study of necessary conditions to the construction of an inclusive education. he aim of this study was to translate and atapt a simple scale used to measure social attitudes toward the inclusion of blind students. From the translation, it was developed a version for each of four disabilities categories: hearing disability, physical disability, intelectual disability and visual impairment. he 637 participants answered a version of this scale and one of the ELASI (Escala Likert de Atitudes Sociais em relação à Inclusão) forms. hese participants were students of several Special Education specialization courses given in the State of Paraná. Most of them were Basic Education teachers. he results indicated a high correlation between the form A ELASI scores and the scores of each of the speciic scale version. In form B there were no signiicant correlations found relating to the visual and hearing disabilities. Moreover, the scale was capable to identify diferences between the disabilities categories. More complete assessments and new studies are necessary to clarify the divergence found between the A and B forms of ELASI.

Uma adequada compreensão das atitudes sociais em relação à inclusão faz parte integrante do estudo das condições necessárias para a construção da educação inclusiva. Este estudo teve por objetivo traduzir e adaptar uma escala simples utilizada para a mensuração de atitudes sociais em relação à inclusão de alunos cegos. A partir da tradução foi elaborada uma versão para cada uma das quatro categorias de deiciências: auditiva, física, intelectual e visual. Cada um dos 637 participantes respondeu a uma versão dessa escala e a uma das formas da Escala Likert de Atitudes sociais em relação à Inclusão (ELASI). Esses participantes eram alunos de vários cursos de especialização em Educação Especial ministrados no Estado do Paraná. A maioria era professores da Educação Básica. Os resultados indicaram uma alta correlação entre os escores da ELASI forma A e os de cada uma das versões da escala especíica. Já na forma B não foram encontradas correlações signiicantes em relação às deiciências auditiva e visual. Adicionalmente, a escala foi capaz de identiicar diferenças entre as categorias de deiciências. Análises mais completas e novos estudos são necessários para esclarecer a divergência encontrada entre as formas A e B da ELASI.
Social attitudes scale toward inclusion: specific version to each disability category